2008
DOI: 10.1158/1940-6207.capr-08-0078
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Characteristics of Cancers Detected in the Prostate Cancer Prevention Trial: Implications for Prostate Cancer Detection and Chemoprevention

Abstract: The Prostate Cancer Prevention Trial (PCPT) showed a risk of prostate cancer at prostatespecific antigen (PSA) <4.0 ng/mL and that prostate cancer risk is reduced by finasteride. A major concern about early detection by PSA and prevention by finasteride is that they may involve biologically inconsequential tumors. We reviewed the pathologic characteristics of prostate biopsies from men in the placebo and finasteride groups of the PCPT. We examined tumor pathology characteristics stratified by level of PSA for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 35 publications
1
48
0
1
Order By: Relevance
“…1 Although initially the development of high-grade PCa under finasteride treatment was viewed as a detrimental effect, 1 recently published new analyses demonstrated this to be an artifact, and in fact, these analyses suggest overall a 30% reduction in the period prevalence of PCa under finasteride with no increased risk for high-grade cancer. [2][3][4][5] Dutasteride 6 is also currently being evaluated in phase III placebo-controlled trials. As additional clinical data become available regarding the benefits and risks of these pharmacologic agents, an examination of their economic impact will also be important.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although initially the development of high-grade PCa under finasteride treatment was viewed as a detrimental effect, 1 recently published new analyses demonstrated this to be an artifact, and in fact, these analyses suggest overall a 30% reduction in the period prevalence of PCa under finasteride with no increased risk for high-grade cancer. [2][3][4][5] Dutasteride 6 is also currently being evaluated in phase III placebo-controlled trials. As additional clinical data become available regarding the benefits and risks of these pharmacologic agents, an examination of their economic impact will also be important.…”
Section: Introductionmentioning
confidence: 99%
“…New PCPT analyses reported in CaPR, however, have renewed hope for hormonal prostate cancer prevention with finasteride. These analyses found that finasteride prevented clinically meaningful disease and did not increase aggressive disease (87)(88)(89)(90), possibly eventually eliminating the related obstacles to finasteride acceptance (86). The case for this agent class has been further strengthened by very recently reported results of a trial of another 5α-reductase inhibitor, dutasteride.…”
Section: Chemopreventionmentioning
confidence: 98%
“…Indeed, !50% of men who have undergone a biopsy in response to a PSA reading of O4.0 ng/ml are diagnosed with PCa (Grubb et al 2008, Schroder et al 2009). Secondly, w15% of men with a 'negative' PSA reading (0-4 ng/ml) have PCa (Thompson et al 2004, Lucia et al 2008. Finally, and most importantly, large randomized trials in the USA and Europe have demonstrated that PSA screening contributes heavily to the overdiagnosis and overtreatment of PCa (Andriole et al 2009, Schroder et al 2009).…”
Section: Circulating Mirnas As Novel Biomarkers Of Pcamentioning
confidence: 99%